PRAWO I SĄDY NA LITWIE W 1812 ROKU W ŚWIETLE „DZIENNIKA CZYNNOŚCI TYMCZASOWEGO RZĄDU LITEWSKIEGO” - Sławomir Godek (Zeszyty Prawnicze)
THE LAW AND THE COURTS IN LITHUANIA IN 1812 IN THE LIGHT OF THE OFFICIAL JOURNAL OF THE ACTIVITIES OF THE PROVISIONAL GOVERNMENT OF LITHUANIA